Eficacia en campo de dos fungicidas para el control del "mal del pie" de la judia (Phaseolus vulgaris L.) en la Bañeza (Leon) - Campelo, M.P.=700 1 Lorenzana, A.; Marcos, M.F.; Amez, M.; Boto, J.A.; Casquero, P.A.
(En, Es)
Ilus., 38 ref.
Keywords: FUSARIUM SOLANI; PHASEOLUS VULGARIS; ENFERMEDADES FUNGOSAS; CONTROL DE ENFERMEDADES; FUNGICIDAS; CARBENDAZIMA; SINTOMAS; RENDIMIENTO; ESPAÑA; JUDIA; MAL DEL PIE